2014
DOI: 10.3109/09286586.2014.949783
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fenofibric Acid on Diabetic Macular Edema: The MacuFen study

Abstract: Subjects treated with fenofibric acid had a modest improvement in TMV, although the study was probably underpowered to detect a benefit over placebo after 1 year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 27 publications
1
23
0
Order By: Relevance
“…Although 1 study showed that individuals with DME receiving fenofibric acid achieved modest improvement in total macular volume on optical coherence tomography compared with placebo, no difference was seen between the 2 groups in relation to worsening of DME or progression of hard exudates on fundus photography. 35 Likewise, there was no significant difference in the severity of DME in either group (relative risk, 1.18; 95% CI, 0.75e1.86; P ¼ 0.48) (Fig 7).…”
Section: Cross-sectional Studiesmentioning
confidence: 83%
See 3 more Smart Citations
“…Although 1 study showed that individuals with DME receiving fenofibric acid achieved modest improvement in total macular volume on optical coherence tomography compared with placebo, no difference was seen between the 2 groups in relation to worsening of DME or progression of hard exudates on fundus photography. 35 Likewise, there was no significant difference in the severity of DME in either group (relative risk, 1.18; 95% CI, 0.75e1.86; P ¼ 0.48) (Fig 7).…”
Section: Cross-sectional Studiesmentioning
confidence: 83%
“…11 Furthermore, 80% of those in the ophthalmology substudy had no or questionable diabetes-related retinopathy at baseline and thus represented a low-risk group for progression, making it likely that the study had limited power to explore the outcomes. The MacuFen study 35 reported that individuals with DME who received fenofibric acid showed modest improvement in total macular volume on optical coherence tomography compared with placebo; however, no difference was seen between the 2 groups in relation to worsening of DME or progression of hard exudates on fundus photography. The authors postulated that the study was underpowered to detect any benefit over placebo and suggested further studies to confirm any long-term benefit of fenofibric acid.…”
Section: Effect Of Lipid-lowering Therapy On Diabetic Macular Edemamentioning
confidence: 96%
See 2 more Smart Citations
“…The ACCORD Eye study included all ACCORD participants who did not have a history of laser photocoagulation or vitrectomy for DR in either eye at baseline [9]. Patients (n = 2856) were monitored for 4 years using fundus photographs, which were graded on the 10-step ETDRS severity scale as follows: no retinopathy (step 1), micro-aneurysms only (steps 2-3), mild nonproliferative DR (NPDR) (steps 4-5), moderate NPDR (steps 6-7), moderately severe NPDR (steps 8-9), and severe NPDR or PDR (steps [10][11][12][13][14][15][16][17]. The primary outcome was the composite end point of the occurrence of three or more steps of progression on the ETDRS severity scale or development of proliferative DR necessitating photocoagulation or vitrectomy.…”
Section: The Accord Eye Studymentioning
confidence: 99%